The Classification of Sex : Alfred Kinsey and the Organization of Knowledge - Drucker, Donna J. (Book collections on Project MUSE., 2014)
"Drucker develops a synthetic argument about how Kinsey's scholarship and training as an entomologist and evolutionary scientist affected his teaching, research, writing, and analysis of human behavior. Places Kinsey at the center of trends in American intellectual and scientific life in the mid-twentieth century. Drucker uses the whole of Kinsey's intellectual life to address questions of data collection and scientific objectivity, and whether it is possible to have research approaches and frameworks for studying human sexuality that could satisfy ever-shifting delineations and measurements of objectivity"--